Crystallization of interesterified soybean oil using a scraped surface heat exchanger with high intensity ultrasound. (December 2019) - da Silva, Thais Lomonaco Teodoro; Martini, Silvana
Abstract: The aim of this research is to crystallize a low saturated interesterified soybean oil (IESBO) using a scraped surface heat exchanger (SSHE) combined with high intensity ultrasound (HIU). The SSHE operated at a flow rate of 3.125 mL/s, crystallization temperature of 32 °C, pressure of 2 bars, and barrels/pin worker speed of 344/208 rpm, respectively. HIU was applied at amplitudes between 20 and 80% using continuous, 5 s or 10 s pulses. The microstructure, melting behavior, rheology, hardness, and oil binding capacity (OBC) of the samples were evaluated. Non-sonicated sample resulted in a crystalline network characterized by 8.9 μm diameter crystals, elasticity values of 25, 255Pa, hardness values of 1.3N and OBC values of 61%. Sonication using 50% amplitude for 5 s was the most efficient condition and resulted in a decrease in crystal size to 4.5 μm, an increase in elasticity values to 100, 238Pa, and an increase in hardness and OBC values to 3.7N and 81.3%, respectively. Highlights: High intensity ultrasound (HIU) was coupled to a scraped surface heat exchanger system. HIU was applied continuously or under pulses using different amplitudes (20%–80%). HIU improved the hardness, elasticity, and oil binding capacity of a low saturated fat. HIU also reduced the crystal size of the sample.